Effect of cryotherapy on postoperative pain: Randomized controlled trial - Atul Jain; Shivani Chauhan; Rachana Bahuguna; Abhinay Agarwal; Rohit Sharma; Faisal Khan (Wolters Kluwer Medknow Publications, 2021)
Context: Postoperative pain(POP) as a consequence of root canal preparation, is a major side effect, of endodontic treatment. It can be prevented by the use of cryotherapy. This randomized control trial was carried out, to test the latter's efficacy, so that it can be recommended, as a preventive measure for POP, during endodontic treatment. Aims: To evaluate the effect of cryotherapy on post-operative pain (POP) during endodontic treatment. Setting and design: Randomized controlled trial was conducted on 40 patients based on inclusion and exclusion criteria [Table 1] in mandibular premolars, diagnosed with symptomatic irreversible pulpitis and normal periapical tissues. Methods & Material: 40 patients were randomly distributed into two groups, Experimental and Control. In the experimental group, 10ml cold saline solution, at -, while in the control group, 10ml of saline solution at room temperature, was used as the final irrigant. Patients were asked to fill a questionnaire, pre-operatively and post-operatively at 6, 24, 48 and 72 hours. Statistical analysis: The obtained data was subjected to statistical analysis using SPSS version ' .0' software. Results: Incidence and intensity of POP, was found to be lower in patients treated with cold saline. Conclusion: Use of cold saline solution as final irrigant, during endodontic treatment, reduces the incidence and intensity of post endodontic pain.